TIME MANAGEMENT - AN INSTRUMENT TO IMPROVE PRODUCTIVITY - Nortje, Johan (The South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: TIME is an Important element in any persons life as a plannlng mechanlsm to meaningfully organIse activities, or to ensure that a oroject runs WIth but also as a generator of destructive forces over it is lost. In the process of growth and progress ln a dynamIC everchanging envIronment. tIme not only becomes dearer to management, but also carcet-, and an era of "time poverty" is experienced by many. A varIety of uncontrollable factors may be the cause of such problems, but a danger eXIsts that those factors over which control may be exercised could be lost within the uncontrol labie ones. The objective of this artIcle on tIme management is then to assist in identIfying those "barriers" which lead to "time pover’ty", how to avoid and prevent tIme wastage and apply methods, and make use of ways to promote the effective use of tIme. AFRIKAANSE OPSOMMING: TYD is ’n belangrlke faktor In dIe lewe van dIe mens enersyds dlen dlt as ’n beplannlngsmeganlsme am jOU daaglikse aktiwitelte slnvol te orden of am ’n pro.lek met preS1Sle te laat verloop, maar andersvds kan dlt ook vernietigende kragte genereer lndlen ’n mens daaroor beheer verloor. In die proses van groel en voorultgang In ’n dinamles veranderende omgewlng, raak dIe tyd van bestuur nle aIleen kosbaarder n ie, maarook skaar’ser en ’n era van’ tydarmoede’ word deur ba i e ervaar